Sistem Informasi Manajemen Organisasi Pemuda Peduli Anak Yatim (Popay) Berbasis Website Responsive - Rinaldi, Syahwan; Rahmawati, Diah; Nugroho, Asep Hardiyanto (UNISTEK, 2022)
Popay (Youth Cares for Orphans) is a non-profit organization that collects, manages, and distributes aid to orphans in the form of cash and basic materials for daily needs. So far, the process of recording and collecting data carried out by the organization uses the traditional model, where all data and transaction records are still using paper and are vulnerable to loss or damage due to poor management of records. To increase the effectiveness and efficiency of data management in the Popay organization, a website-based data processing information system was created. At the stage of making this website, the Rapid Application Development (RAD) development method was used. This system is designed to be responsive so that it can adapt optimally to any device. The importance of adjusting the display design to the screen of the device used in order to provide convenience to organizational administrators when filling in data for orphans from house to house, as well as for donors who want to access information without need for special devices such as laptops. With the management information system in the Popay organization, it helps the organization's management in managing data systematically and makes it easier for the public as well as donors to obtain activity information and reports on the use of funds.